Empowerment of Community Economic Mentored by UP2K Padasuka Village, Cibeunying Kidul District Through Improving Ornamental Fish Farming Skills for Export - Rizal Ramdan Padmakusumah; Ismail Solihin; Ryan Kurniawan; Kahfi Cakra Wiguna; Haura Khairunnisa; Ridha Amalia Sholehat (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
This article is an article resulting from community service activities (PKM) organized by the Faculty of Economics and Business, Widyatama University in collaboration with partners, namely the Family Welfare Improvement Effort (UP2K) PKK, Padasuka Village, Bandung City. The PKM activity carried out is training aimed at empowering the community's economy and/or businesses fostered by UP2K, Padasuka Village in the form of increasing the ability to raise or cultivate ornamental fish for export purposes. The stages of implementing the activities carried out consist of 6 stages including (1) pre-survey, (2) proposal preparation, (3) preparation, (4) implementation, (5) monitoring and evaluation, and (6) preparation of activity reports. The participants in this training activity were 45 people. The training activities carried out were in the form of presentations of material from expert speakers accompanied by discussions or questions and answers as well as simulations or demos. The results are also the main conclusions of the PKM activities carried out, namely that ornamental fish cultivation and export business is a promising business for residents or businesses fostered by UP2K of Padasuka Village. The initial stage of starting a business for participants after training is the cultivation of brushmouth black slayer fish and brushmouth albino slayer fish in groups. Some suggestions for similar PKM activities or future developments include providing initial business capital and bringing in international speakers or participants.